2015
DOI: 10.3390/su71215852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Employees’ Work Values and Organizational Management on Corporate Performance for Chinese and Taiwanese Construction Enterprises

Abstract: Through questionnaire surveys, this study explored the discrepancies in work values and organizational management between employees and cadre members of construction enterprises on the two sides of the Taiwan Strait. Statistical methods including data reliability, regression analysis, and tests of significance were utilized for modelling a case study. The findings of this study included:(1) in terms of work values, employees from China focused on their lives "at present", while those from Taiwan focused on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Specifically, a manager will use his or her abilities, knowledge base, experiences, and perspectives to increase the productivity of those with whom they manage (Hartzell, 2019).On the other hand, strong work ethics and values play an essential role in the workplace (Reddy, 2016). Further, Lin, Shen, and Hsu (2015) asserted that understanding employees' work values had become a key concern or issue for organizations that aim to achieve higher performances.…”
Section: ___________________________________________________________________________ 1background Motivation and Objectivesmentioning
confidence: 99%
“…Specifically, a manager will use his or her abilities, knowledge base, experiences, and perspectives to increase the productivity of those with whom they manage (Hartzell, 2019).On the other hand, strong work ethics and values play an essential role in the workplace (Reddy, 2016). Further, Lin, Shen, and Hsu (2015) asserted that understanding employees' work values had become a key concern or issue for organizations that aim to achieve higher performances.…”
Section: ___________________________________________________________________________ 1background Motivation and Objectivesmentioning
confidence: 99%
“…The work values of employees are different in each generation (Lin 2015). The work values of employees should be understanding by organization because it will help organization in achieving higher performance.…”
Section: Work Valuesmentioning
confidence: 99%
“…Research conducted in China and Taiwan conducted by Lin et al (2015) found that there are differences in the values of work between the two countries. Available six work values are used, namely quality of life, dreams, wealth, not feeling confused at work, opportunities to continue study and promotion opportunities.…”
Section: Work Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…As organisations have different organisational culture and values, so do individuals attach different levels of importance and value to the tasks that they are employed to perform (Lin et al, 2015). Such beliefs, ideas and conceptions are referred to as 'work-values' which may likely differ, among individual employees within the same organisation.…”
Section: Introductionmentioning
confidence: 99%